Interactive Learning Online at Public Universities: Evidence from a Six‐Campus Randomized Trial. (16th October 2013) - Bowen, William G.; Chingos, Matthew M.; Lack, Kelly A.; Nygren, Thomas I.
Abstract Online instruction is quickly gaining in importance in U.S. higher education, but little rigorous evidence exists as to its effect on student learning. We measure the effect on learning outcomes of a prototypical interactive learning online statistics course by randomly assigning students on six public university campuses to take the course in a hybrid format (with machine‐guided instruction accompanied by one hour of face‐to‐face instruction each week) or a traditional format (as it is usually offered by their campus, typically with about three hours of face‐to‐face instruction each week). We find that learning outcomes are essentially the same—that students in the hybrid format are not harmed by this mode of instruction in terms of pass rates, final exam scores, and performance on a standardized assessment of statistical literacy. We also conduct speculative cost simulations and find that adopting hybrid models of instruction in large introductory courses has the potential to significantly reduce instructor compensation costs in the long run.